14-2(4x-8)=6

Simple and best practice solution for 14-2(4x-8)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14-2(4x-8)=6 equation:


Simplifying
14 + -2(4x + -8) = 6

Reorder the terms:
14 + -2(-8 + 4x) = 6
14 + (-8 * -2 + 4x * -2) = 6
14 + (16 + -8x) = 6

Combine like terms: 14 + 16 = 30
30 + -8x = 6

Solving
30 + -8x = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-30' to each side of the equation.
30 + -30 + -8x = 6 + -30

Combine like terms: 30 + -30 = 0
0 + -8x = 6 + -30
-8x = 6 + -30

Combine like terms: 6 + -30 = -24
-8x = -24

Divide each side by '-8'.
x = 3

Simplifying
x = 3

See similar equations:

| 6(x+3)+6=42 | | 2x+3=5x+8 | | 5r^2-20r-9=6 | | 3w(11w+8)= | | 5r^2-20r-9=0 | | 13.62+.13(x+3)=14.37-.09x | | xsquare(x+5)(x-5)=0 | | 1600x=20 | | 3y+17=62 | | y+19=192 | | f(-6)=7-2x | | 4x+14=5x | | 2x=6(2x-2)-5 | | 13.62+.13(x+3)=14.37+.09x | | 3(3+1)=(9-2x) | | 6n=(n+5) | | 30=-8x+2(x-6) | | y=mx+bfindx | | x^1/4=2 | | 5x-15=2x+20 | | 90+3+x+x-8=180 | | 10n-0.75=0.1n-0.375 | | 2-7g=2-g | | 2e^3x-9=0 | | 12a=3a+2.5a+a | | -1=6x-31 | | 15.93+.09(x+3)=16.43-.13x | | -3(3y-7)+2(2y+8)= | | 2[-2(4x+5)+4(3x-4)]= | | z/3=11 | | 5x-7=2x-14 | | 7/3.7/5 |

Equations solver categories